Leveraging Digital Science for Improved QA Methodologies - Mothey, Mouna (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Products and processes are using digital technology to increase manufacturing efficiency and quality. The digital revolution of the industrial industry is primarily driven by intense competition and changing customer expectations. Manufacturers may improve customer experiences, save costs, and boost speed and efficiency by using digital technologies. The application of related individual digital technologies has not been thoroughly assessed and combined to achieve adequate QA in the building sector, and as a result, it has received limited attention, despite the expanding rich and fragmented literature focusing on Industry 4.0 and Quality Assurance (QA). Therefore, the purpose of this study was to collect, assess, and synthesize the existing literature on specific digital technology uses in quality assurance in the construction sector and suggest future lines of inquiry. Deming's cycle concept and a literature review methodology were used in this study to answer the following four research questions: (1) what is the literature's current state-of-the-art? (2) Which digital tools have been used in the construction sector for quality assurance? (3) Which QA process areas have seen the use of digital technology, and what are their uses? (4) What are the shortcomings of the current study and potential avenues for further investigation into digital technology for quality assurance in the construction sector? According to the data, since 2017, there has been a growing trend of study on digital technologies for quality assurance in the construction industry. Using six distinct study methodologies published throughout 18 different publishing sources, this spans 23 nations. Based on their functionality, four types of digital technologies were identified as having been used for quality assurance in the construction industry: data gathering technologies, decision-oriented technologies, collaboration technologies, and technologies linked to security and transparency. The use of digital technologies have a high degree of application during the "do" phase, enhancing the quality management procedure throughout construction towards reaching pre-stated quality standards, according to evaluation using Deming's cycle framework.